Manajemen Isu Pemerintah Desa Mpanau Kecamatan Sigi Biromaru Terkait Informasi Dana Bantuan Langsung Tunai bagi Masyarakat yang Terkena Dampak Covid-19 - Lestari, Winda (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to determine the management of issues related to cash stimulus carried out by the Village Government of Mpanau Kec. Sigi Biromaru. This study uses a qualitative method on the basis of case study research. Research data obtained through observation, in-depth interviews. The analysis used is data collection, data reduction, data presentation and conclusion. The results of this study are: 1. Identification of issues, forms a special team to monitor issues in the community environment; 2. Analyzing issues, three issues that have a major impact are delays in distribution, unilateral changes to the list of beneficiaries and changes in the amount of funds; 3. Strategies for responding to issues, educating the community through outreach, deliberations on determining the list of beneficiaries in a transparent manner and tightening the implementation of the distribution; 4. Implementation of the program, socialization is carried out by the Village Head and all persons in of assistance to the Mpanau Village community, holding large deliberations in transparently select prospective beneficiaries and tighten the distribution; and 5. Evaluate, continue to modify the preparation of the strategy and its implementation to increase public trust.